1993
DOI: 10.1128/iai.61.10.4326-4332.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cation flux studies of the lesion induced in human erythrocyte membranes by the thermostable direct hemolysin of Vibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus, an important agent of seafood-borne gastroenteritis, expresses several putative virulence factors that could account for the disease symptoms of infected humans, namely, diarrhea, nausea, and abdominal cramps. The pathogenicity of V. parahaemolyticus correlates well with the Kanagawa phenomenon (the hemolytic ability of strains grown on Wagatsuma blood agar), implicating the thermostable direct hemolysin (TDH) as the predominant toxin responsible for pathogenicity. TDH-induced hemolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…This is a very important observation in the context of TDH induced cationic fluxes playing a major role in the diarrhetic action of Vibrio parahaemolyticus . Our observations with the cationic selective pore response clearly match to the erythrocyte model studies .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This is a very important observation in the context of TDH induced cationic fluxes playing a major role in the diarrhetic action of Vibrio parahaemolyticus . Our observations with the cationic selective pore response clearly match to the erythrocyte model studies .…”
Section: Resultssupporting
confidence: 86%
“…In future experiments, the influence of anions on the transmembrane current induced by TDH2 at different voltages will be studied to analyze whether TDH2 has a preferential selectivity of anions over cations. Preferential selectivity of potassium over sodium by TDH2 induced pores supports the previous hypothesis . In their study over the human erythrocyte membranes, Huntley et al has showed that TDH induced hemolysis was highly selective for potassium ions over sodium.…”
Section: Resultssupporting
confidence: 63%
“…The present study reveals that thermostable direct haemolysin from V. parahaemolyticus induces a cation channel. In earlier flux studies (Huntley et al, 1993), a sequence of Cs + > Li + > K + > Rb + > Na + has been Fig. 6.…”
Section: Resultsmentioning
confidence: 92%
“…This permeabilization to calcium ions could result from the formation of pores on the cell membrane. In erythrocytes, TDH has been reported to acts as a poreforming toxin (11,13,23) causing membrane permeabilization and colloidal osmotic lysis. However, although TDH has been reported to induce calcium influx in cells other than erythrocytes (10,18,24), formation of pores in such cell lines has not been reported.…”
Section: Discussionmentioning
confidence: 99%